2012
DOI: 10.5387/fms.58.17
|View full text |Cite
|
Sign up to set email alerts
|

Local Application of Nucleus Pulposus Induces Expression of P2x3 in Rat Dorsal Root Ganglion Cells

Abstract: : The P2X 3 receptor is a ligand -gated cation channel that is activated by extra cellular adenosine triphosphate (ATP) found in the dorsal root, trigeminal and nodose ganglia. It is one of the receptors transmitting nociceptive information of injuries and inflammation of the periphery by endogenous ATP released from damaged cells. The present study was performed in order to evaluate if there was an increased expression of P2X 3 -immunoreactivity in dorsal root ganglion (DRG) neurons after experimental disc he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Still, a significant increase in the expression of TNF, CX3CL1, and CX3CR1 was demonstrated, supporting the previous observation that local application of NP onto the primary afferents may change the gene expression in the DRGs [37]. The changes in gene expression were only observed on the ipsilateral side.…”
Section: Discussionsupporting
confidence: 87%
“…Still, a significant increase in the expression of TNF, CX3CL1, and CX3CR1 was demonstrated, supporting the previous observation that local application of NP onto the primary afferents may change the gene expression in the DRGs [37]. The changes in gene expression were only observed on the ipsilateral side.…”
Section: Discussionsupporting
confidence: 87%
“…Recent reports have shown an increase in P2X3R expression in primary sensory afferents [19,20]. In addition, local application of nucleus pulposus induces expression of P2X3Rs in rat dorsal root ganglion cells [9], suggesting a role for P2X3Rs in disc herniation and sciatica. However, the mechanism underlying P2X3R upregulation under LDH conditions remains largely unknown.…”
Section: Introductionmentioning
confidence: 90%
“…Inflammatory reactions between nucleus pulposus (NP) and the nerve roots have been suggested to play an important role in disc herniation with sciatica [1][2][3][4][5]. Experimental studies have demonstrated that epidural application of NP leads to pronounced morphologic and functional changes in the nerve roots [6][7][8][9]. However, the pathogenic mechanisms linking herniated NP, gene expression, and pain hypersensitivity are not well understood.…”
Section: Introductionmentioning
confidence: 99%